Management of Village Fund Allocations from an Islamic Economic Perspective - Agustin, Ela; Mawardi; Abizar (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The management of village fund allocation is still not optimal in accordance with the objectives of Village Fund Allocation (ADD). The purpose of Village Fund Allocation (ADD) is to finance village government programs in carrying out government activities and empowering the population. The aim of this research is to determine the Management of Village Fund Allocation (ADD) from an Islamic Economic Perspective in Sukajaya Village, Anak Ratu Aji District, Central Lampung Regency. The research method used is descriptive qualitative research. Data collection techniques were carried out through observation, interviews and documentation methods. The results of the research show that the Management of Village Fund Allocations in Increasing Development in Sukajaya Village, Anak Ratu Aji District, Central Lampung Regency, goes through three stages, namely planning, implementation and accountability. The management of Village Fund Allocations in Sukajaya Village is reviewed from Islamic Economics, in the Planning, Implementation and Accountability stages in Sukajaya Village there are still many who have not followed the procedures in Islamic development economics.